2019
DOI: 10.21037/jtd.2019.12.10
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the classification accuracy of a deep learning framework-based computer-aided diagnosis system in different pathological types of breast lesions

Abstract: Background: Deep learning-based computer-aided diagnosis (CAD) is an important method in aiding diagnosis for radiologists. We investigated the accuracy of a deep learning-based CAD in classifying breast lesions with different histological types. Methods: A total of 448 breast lesions were detected on ultrasound (US) and classified by an experienced radiologist, a resident and deep learning-based CAD respectively. The pathological results of the lesions were chosen as the golden standard. The diagnostic perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 28 publications
(30 reference statements)
0
16
0
Order By: Relevance
“…Several reports have described applying different types of CAD to breast ultrasound [6,[19][20][21]. These studies all reported that the CAD systems enhanced the diagnostic performance of breast ultrasound, especially specificity and accuracy.…”
Section: Principal Findingsmentioning
confidence: 99%
“…Several reports have described applying different types of CAD to breast ultrasound [6,[19][20][21]. These studies all reported that the CAD systems enhanced the diagnostic performance of breast ultrasound, especially specificity and accuracy.…”
Section: Principal Findingsmentioning
confidence: 99%
“…AI models increase radiologists’ classification specificity in cases where the radiologist has already detected a lesion ( 83 - 85 ). Some lesions in the breast could, however, be missed by the radiologist ( 86 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies validate the performance of DL algorithms [197]- [199] using expert inference, showing that DL algorithms can greatly help radiologists. This is mostly in cases where the lesion was already detected by an expert, and the DL model is used to classify them.…”
Section: Digital Mammography and Digital Breast Tomosynthesis (Mm -Dbt)mentioning
confidence: 91%